PERAN KETELADANAN GURU PENDIDIKAN AGAMA KRISTEN TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK DI DITINJAU DARI (YOHANES 13 AYAT 15). - Ndun, Yusak; Saudila, Jane (Sekolah Tinggi Teologi Pelita Hati, 2025)
This study aims to analyze the role of exemplary behavior of Religious Education teachers (PAK) in shaping the character of students, with reference to John 13:15. This verse emphasizes the importance of Christ's example in the lives of His followers, which is relevant in the context of education, particularly in cultivating the character of students. The exemplary behavior of PAK teachers becomes a strategic factor in instilling Christian values such as love, honesty, humility, and responsibility in students. This study asserts that the exemplary behavior of PAK teachers has a transformative impact on shaping the character of students, as demonstrated by Jesus in John 13:15.